4/ Actuele Kunstmarkt. (Brussel : Vereniging der Belgische Galerijen voor Actuele Kunst, 1974)
Acconci, Vito ; Flavin, Dan ; Oppenheim, Dennis ; Rauschenberg, Robert ; Raynaud, Jean-Pierre ; Smerck, Daniel ; Appel, Karel ; Castillo, Jorge ; Denis, Alain ; Vereecke, Amand ; Huebler, Douglas ; Gilbert & George ; Klasen, Peter ; etc.
4/ Actuele Kunstmarkt, Casino, Knokke, 19.5. tot 16.6.1974
boek